Значення загальних принципів права у правозастосовчій діяльності міжнародних судів - Юхимюк, О.; Yuhymiuk, О. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проведено аналіз ролі загальних принципів права, визнаних цивілізованими націями, у правозастосовчій діяльності міжнародних судових інстанцій в умовах динамічного зростання відповідних інституцій. З’ясовано, що правозастосовна діяльність нових міжнародних чи регіональних судових або квазісудових інституцій сприяє формуванню нового розуміння загальних принципів права та утвердженню їх вагомості у вирішенні міжнародних та міждержавних спорів. The article highlights the most characteristic feature of the current stage of the international judicial proceedings development, andalso one of the most hotly debated aspect of this issue – growth in the number of international courts and tribunals. Intense changes in the international justice gave rise to a number of new challenges, such as fragmentation of international law, functionalism and regionalization, as well as the very jurisdiction of the Court (Tribunal). The study proves that the general principles of law play role of a consolidating factor that can contribute to the unification of the law enforcement proceeding performed by both international judicial bodies and quasi-judicial ones. General principles of law comprise the most fundamental legal principles which are a precondition for functioning of the rule of law. Since the beginning the general principles of law have been of prior significance forthe international bodies dealing with settling the disputes in making their decisions. General principles of law, recognized by all civilized nations, serve as an independent source of law, alongside with international agreements or international customs. The author concludes that the dynamic development of humanity and the international law can affect the content of thegeneral principles of law.
Significance of the General Legal Principles in the International Courts LawEnforcement Activity
Keywords: загальні принципи права; міжнародний суд; джерела міжнародного права; general principles of law; international court sources of international law